Gender Mainstreaming in Arabic Literature - Musgamy, Awaliah; Rusydi, Muhammad; Kurniati, Kurniati (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2020)
Arabic literature is a means of gender mainstreaming which is very rich in gender issues. This is based on the social fact that Arab society in its historical footsteps has a stereotype as a community that is very thick with its patriarchal culture. Consequently, the social condition which is less responsive to gender influences the birth of Arabic literary works in various types in which gender issues such as marginalization of women, subordination of women to men, violence, negative stereotypes, and others. This article is qualitative research by using feminist Arabic literary criticism as a perspective, gender mainstreaming in Arabic literature is carried out by tracing the gender issues that exist in Arabic literature in its various forms. Through feminist Arabic literary criticism, various theories of feminist literary criticism consisting of ideological criticism, gynocritical criticism, socialist criticism, psychoanalytic criticism, ethnic criticism, and lesbian criticism, are applied in transforming and reconstructing gender-responsive relations between men and women.